Equações do 2° grau em variáveis complexas - Batista, Roberto do Nascimento (2018)
In this work a methodology is presented to work on quadratic equations involving complex variables. Firstly, a history of the second-degree equations and complex numbers is presented. Following the formalism involving the functions of second degree and complex numbers is presented. Finally, a didactic sequence is suggested to approach this generalization of the quadratic equation.